Tools for the Assessment of the Laser Printability of Nickel Superalloys - Chechik, Lova; Christofidou, Katerina; Farquhar, Lucy; Tse, Martin; Baxter, Gavin; Todd, Iain (Metallurgical and Materials Transactions A-Physical Metallurgy and Materials Science, 2023)
Additive Manufacturing (AM) is a revolutionary technology with great interest from the aerospace sector, due to the capability of manufacturing complex geometries and repairing of damaged components. A significant volume of research is being conducted with high-temperature alloys, particularly nickel superalloys. However, the high-temperature properties of nickel superalloys are derived from the high fraction of strengthening precipitates, which in turn, lead to poor amenability to additive manufacture. Various cracking modes are common in nickel superalloys, primarily as a result of the high level of alloying and the extreme thermal conditions experienced in AM. Herein, crack susceptibility calculations from literature were critically analyzed and combined, resulting in a simple failure susceptibility that correlates with literature. Currently, the range of alloys which have been tested in AM and reported in literature is limited and lacks a standard methodology, making accurate assessment of printability difficult. Scheil solidification calculations were performed, testing solute trapping (ST) and back diffusion models for both the cooling rates associated with laser powder bed fusion (L-PBF) and laser-directed energy deposition (L-DED). The results confirm that L-PBF exhibits cooling rates that can result in ST, unlike in L-DED. These differences mean that alloys cannot be developed more generally for AM, but must be developed with a specific AM process in mind.
Created from Fastlane, Scopus look-up